Clinical and Angiographic Outcomes of SCBs versus PCBs in Coronary Artery Disease: A Comprehensive Meta-Analysis - Muhammad Daoud Tariq, Muneeba Ahsan, Samaha Khalid, Malik Aon Ali Abbas, Rimsha Adnan, Hritvik Jain (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Coronary artery disease (CAD) remains a leading global cause of mortality, with percutaneous coronary intervention (PCI) as a key treatment. Although drug-eluting stents (DES) have reduced restenosis, in-stent restenosis (ISR) persists. Drug-coated balloons (DCBs), particularly sirolimus-coated balloons (SCBs), offer a promising alternative to paclitaxel-coated balloons (PCBs) due to superior pharmacologic properties. This meta-analysis evaluates the safety and efficacy of SCBs versus PCBs in ISR and de novo coronary lesions. Objective: 1. To synthesize evidence comparing SCBs and PCBs in coronary artery disease.. 2. To evaluate whether SCBs offer superior clinical and angiographic outcomes, including TLF, MI, TLR, LLL, and MLD.. Methods: A thorough search was performed throughout PubMed, Embase, Web of Science, Scopus, Google Scholar, and Cochrane. Angiographic results included diameter stenosis, in-segment LLL, and MLD; clinical results included TLF, cardiac mortality, TVMI, and TLR. CMA software's random-effects model was used to compute pooled odds ratios (ORs) and standardised mean differences (SMDs) with 95% CIs. At p < 0.05, statistical significance was established. Results: Six RCTs and four observational studies with a total of 6,256 participants were included in this meta-analysis. The pooled analysis revealed that there was no statistically significant difference in TLR (OR: 0.986, 95% CI: 0.800–1.215, p = 0.894; I² = 0%), cardiac death (OR: 0.825, 95% CI: 0.351–1.937, p = 0.658; I² = 0%), MI (OR: 0.603, 95% CI: 0.299–1.215, p = 0.157; I² = 0%), and TLF (OR: 1.006, 95% CI: 0.813-1.245, p = 0.957) between the two intervention groups. Although not statistically significant, SCBs demonstrated better angiographic outcomes including lower LLL (SMD: –0.180, 95% CI: –0.420 to 0.060, p = 0.141), greater MLD ( SMD: 0.112, 95% CI: –0.055 to 0.280, p = 0.188), and lower diameter stenosis (SMD: –0.088, 95% CI: –0.334 to 0.158, p = 0.484). Conclusion: Although SCBs and PCBs demonstrated comparable efficacy and safety and efficacy in patients undergoing PCI, current evidence suggests that SCBs may lead to superior angiographic outcomes. Further well-designed, large-scale trials are needed to validate these findings and improve clinical guidelines. Keywords: Sirolimus-coated balloon, Paclitaxel-coated balloon, In-stent restenosis,Percutaneous coronary intervention